Systematic analysis of lysine crotonylation in human macrophages responding to MRSA infection - Zhang, Hao; Ma, Wei; Liu, Haoru; Tang, Wanqi; Shu, Junjie; Zhou, Jianping; Zheng, Hongsheng; Xiao, Hongyan; Yang, Xue; Liu, Daoyan; Liang, Huaping; Yang, Xia (Frontiers in Cellular and Infection Microbiology, 2023)
Methicillin-resistant Staphylococcus aureus (MRSA) is one of the most commonly encountered bacteria found in healthcare clinics and has been ranked a priority 2 pathogen. Research is urgently needed to develop new therapeutic approaches to combat the pathogen. Variations in the pattern of protein posttranslational modifications (PTMs) of host cells affect physiological and pathological events, as well as therapeutic effectiveness. However, the role of crotonylation in MRSA-infected THP1 cells remains unknown. In this study, we found that crotonylation in THP1 cells was altered after MRSA infection. It was then confirmed that lysine crotonylation profiles of THP1 cells and bacteria were different; MRSA infection inhibited global Kcro modification but partially elevated lysine crotonylation of host proteins. We obtained a proteome-wide crotonylation profile of THP1 cells infected by MRSA further treated by vancomycin, leading to the identification of 899 proteins and 1384 sites down-regulated, and 160 proteins and 193 sites up-regulated. The crotonylated down-regulated proteins were mainly located in cytoplasm and basically enriched in spliceosome, RNA degradation, protein posttranslational modification, and metabolism. However, the crotonylated up-regulated proteins were mainly located in nucleus and significantly involved in nuclear body, chromosome, ribonucleoprotein complex, and RNA processing. The domains of these proteins were significantly enriched on RNA recognition motif, and linker histone H1 and H5 families. Some proteins related to protecting against bacterial infection were also found to be targets of crotonylation. The present findings point to a comprehensive understanding of the biological functions of lysine crotonylation in human macrophages, thereby providing a certain research basis for the mechanism and targeted therapy on the immune response of host cells against MRSA infection.